Reducing health risks from wastewater use in urban and peri-urban sub-Saharan Africa: Applying the 2006 WHO guidelines - Drechsel, Pay; Keraita, Bernard N.; Amoah, Philip; Abaidoo, Robert C.; Raschid-Sally, Liqa; Bahri, Akissa (IWA Publishing, 2008)
Where rapid urbanization is outpacing urban capacities to provide sound sanitation and wastewater treatment, most water sources in city vicinity are heavily polluted. This is of great concern as many of the leafy vegetables eaten raw in the cities are produced in these areas. Following the new WHO guidelines, different non-treatment options at farm, market, and kitchen level were field tested for health risk reduction with special consideration to efficiency and adoption potential. As most households are used to vegetable washing (although ineffectively), an important entry point for risk reduction is the increased emphasis of the new guidelines on food preparation measures. A combination of safer irrigation practices (water fetching, on-farm treatment, and application), the allocation of farmland with better water sources, and improved vegetable washing in kitchens appear to be able to reduce the potential risk of infections significantly, although it might not be possible to reach the ideal threshold without some kind of wastewater treatment. The on-farm trials carried out in Ghana also explored the limitation of other risk reduction measures, such as drip irrigation, crop restrictions and cessation of irrigation under local circumstances considering possible incentives for behaviour change.